Biedronki (Coleoptera: Coccinellidae) odłowione przy użyciu samołówek świetlnych w trzech kompleksach leśnych we wschodniej i centralnej Polsce - Kamiński, Przemysław; Tobiasz, Sebastian; Grochowska, Małgorzata; Baranowski, Artur; Romanowski, Jerzy; Ceryngier, Piotr (Studia ecologiae et bioethicae, 2020)
As an important limiting factor of arthropods harmful to crop plants, ladybird beetles (Coccinellidae) are a frequent subject of entomological research. Various methods have been used to collect them but attracting them via the use of light has rarely been applied. In this study, we used this method to catch ladybirds in the Jata nature reserve (Eastern Poland), and in two forest complexes within the administrative boundaries of Warsaw (Central Poland), namely, the Bielański forest nature reserve, and the Młociński forest. Night catches of ladybirds into light traps took place from April to September in both 2018 and 2019. Altogether, 347 ladybirds belonging to 16 species were collected. The highest ladybird species richness, amounted to 15 species, but also the lowest mean number of ladybird individuals (1.3 per sample) were recorded in Jata. In the Bielański forest, nine species and the average of 4 individuals per sample were recorded, whilst in the Młociński forest, the respective values were four species, and 2.2 individuals per sample. In all three localities, Calvia decemguttata (L.) prevailed. Other species with a relatively high contribution were Harmonia axyridis (Pallas) and Vibidia duodecimguttata (Poda). The majority of the sampled ladybird individuals (71%) belonged to the species having no warning colouration, which may indirectly indicate their nocturnal lifestyle.